Synergistic remediation of Pb contamination in rice field soil with FeMg-LDH@Bentonite and compost: impacts on Pb bioavailability and soil environment - Guan, Xian; Bai, Jing; Yuan, Xing Zhong; Guo, Jian Wei; Liu, Xiaowen (Frontiers in Microbiology, 2026)
IntroductionLead (Pb) contamination in paddy soils can degrade soil quality, increase plant Pb uptake, and disrupt soil microbial communities. This study evaluated integrated remediation using FeMg-LDH@Bentonite (FMLB) and compost, focusing on Pb bioavailability, plant uptake, and microbial community structure.MethodsA pot-based remediation experiment was conducted using Pb-contaminated paddy soil. FMLB and compost were applied at different mixing ratios. Pb bioavailability and soil Pb levels were assessed alongside plant uptake indicators. Soil microbial community structure and alpha-diversity were characterized (e.g., by 16S rRNA gene amplicon sequencing), and soil enzyme activities were measured to reflect soil biological functioning.ResultsPb contamination significantly altered soil properties, reduced soil quality, and impacted microbial diversity. Amendment application reduced Pb bioavailability across treatments, with the greatest reduction observed for the combined treatment of FMLB:compost = 3:7. This optimal combination not only decreased Pb concentrations and plant uptake potential, but also improved microbial indicators: bacterial community composition and α-diversity metrics shifted toward the original soil (OS) reference under identical pot conditions, and enzyme activities were enhanced.DiscussionOverall, combined application of FMLB and compost represents an environmentally sound and potentially cost-effective strategy for remediating Pb-contaminated paddy soils while improving soil fertility and microbial function. Importantly, microbiome responses and selected enzyme endpoints are interpreted as indicators associated with Pb stabilization and improved soil condition, rather than direct evidence of microbially mediated Pb transformation.